Suku Anak Dalam (SAD) Dan 2000 Ha Lahan Kompensasi Dari PT. Asiatic Persada Tahun 2011-2014 - Randy Maulanda; Erniwati Erniwati (Jurnal Kronologi, 2022)
Abstract This study discusses the distribution of compensation land to the Suku Anak Dalam (SAD) in 2011-2014. This study aims to clarify the social life of the SAD community in Bungku Village, including land conflicts and how the government responds in solving land problems. This research includes historical qualitative research using a historical method approach in the form of interviews, literature studies, and archival studies. For writing sources, it is necessary to use a field approach through data documents on recipients of land compensation from the Regent of Batanghari, photos of SAD people, lands that are in conflict, and photos of where SAD and transmigrant communities live in Bungku Village. This article shows that the conflict occurred due to the struggle for land power between SAD and PT. Asiatic Persada, where the company took customary land that belonged to SAD in Bungku Village.